INTERPRETASI PASAL MULTITAFSIR DALAM MENENTUKAN KUALIFIKASI SANKSI DALAM TINDAK PIDANA BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Fifi Ayu Lestari (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2026)
Narcotics abuse in Indonesia is a serious crime that affects the nervous system and causes dependence. Legal subjects range from users to producers. This thesis examines the interpretation and reformulation of Article 112 and Article 127 Paragraph (1) of Law No. 35 of 2009 to provide clear criminal qualifications and legal certainty. Using a normative judicial method, the research highlights that a criminal act occurs when both objective and subjective elements are met. Precise legal formulation is crucial to distinguish the roles of perpetrators, as every prohibited act must carry firm criminal sanctions for offenders.